Surgical Treatment of Dorsolumbar Spine Tuberculosis by Posterior Decompression, Stabilization with Transpedicular Screws and Rods and Fusion - Saha, Apel Chandra; Kabiraj, Snriti Kona; Rahman, Md Rezwanur; Shermin, Shahana; Masud, Md Hasan; Hossain, Muhammad Awlad (Delta Medical College Journal, 2016)
Background: Spinal tuberculosis is a medical disease and antitubercular drugs play the main role in the recovery of patients. However, with proper indication, surgical procedures are superior in the prevention of neurological deterioration, maintenance of stability, early recovery and early mobilization. Modern method of surgical intervention of dorsolumbar tuberculosis is posterior decompression, stabilization with transpedicular screws and rods and fusion. Objective: To evaluate the efficacy of posterior decompression, stabilization by transpedicular screws and rods and fusion in patients with spinal TB in thoracic and lumbar region. Materials and method: This is a prospective interventional study carried out at National Institute of Traumatology & Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh and different private hospitals in Dhaka from October, 2012 to December, 2014. Total number of patients was 12; among them 7 were male and 5 were female, age ranged from 21-60 years with a follow up period of 12 months to 18 months. Results: More common site of tubercular lesion was at dorsal spines (58.73%). In this study the patients were preoperatively classified according to American Spinal Injury Association (ASIA) Impairment Scale and among the patients 1 was ASIA- A, 2 were ASIA-B, 5 were ASIA-C, 3 were ASIA-D, and 1 was ASIA-E. In postoperative state 1 patient was ASIA-B, 3 patients were ASIA-D and 8 were ASIA-E. Maximum patients (75%) had bony fusion grade 1. More than 80% subjects had good outcome. Conclusion: Posterior decompression, stabilization with transpedicular screws and rods and fusion is a satisfactory surgical modality of treatment of dorsolumbar spinal tuberculosis. Delta Med Col J. Jul 2016 4(2): 71-76